PENGARUH METODE PENGOLAHAN TERHADAP KANDUNGAN TANIN DAN SIFAT FUNGSIONAL TEPUNG PROSO MILLET (Panicum miliaceum) - Mahendra, Putu Eka Ditya; Yusasrini, Ni Luh Ari; Pratiwi, I Desak Putu Kartika (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 8 No 4 (2019): Jurnal ITEPA, 2019)
The aim of this research were to determine the effect of processing methods on tannin content, functional properties proso millet ( Panicum miliaceum ) flour and determine which method can produce the lowest tannin content and the best functional properties. The Completely Randomized Design (CRD) was used in this research with 4 type of processing method treatments, such as: direct method, germination method, fermentation method, and germination-fermentation method. The treatment was repeated four times to obtain 16 experimental units. Data from the research results were analyzed by variance and if the treatment had a significant effect, then followed by Duncan’s Multiple Range Test (DMRT). The results showed that the treatment of proso millet processing method had a highly significant effect (P <0.01) on yield, water content, ash content, tannin content, water absorption capacity, oil absorption capacity, swelling power, and solubility. The best treatment was produced by proso millet flour with germination-fermentation processing method was able to produce the lowest tannin content on 0.59% with a yield value 65.47%, water content 12.36%, ash content 1.45%, water absorption capacity 172.85%, oil absorption capacity of 107.73%, swelling power of 10.11 g / g, and water solubility index of 44.10%. Keywords: proso millet , processing method , tannin content , functional properties, flour.